2020
DOI: 10.15407/zoo2020.04.275
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Avian Settlements in Lake Tonga (Northern Algeria)

Abstract: is an integral reserve within the El-Kala National Park, Biosphere Reserve and Ramsar site. This study consists in determining the diversity and phenology status of waterbirds in this reserve over an entire annual cycle (2017-2018). The census was carried out from fixed observation points. Of the 35 species recorded, wintering birds dominate with 12 species (34 %), followed by breeding sedentary species with 11 species (32 %). The breeding water bird populations are dominated by the common coot Fulica atra, (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 14 publications
(14 reference statements)
2
9
0
Order By: Relevance
“…This high amount of dense vegetation provides better conditions for nesting and shelter from predators, notably birds of prey (Rouibi et al, 2013;Gherib andLazli, 2016, 2017;Elafri et al, 2016). This variation in the pattern of waterbird abundance and richness between wintering and breeding seasons in Lake Tonga was also described by Elafri et al (2016) and Loucif et al (2020), but numbers were considerably lower than those reported in this study.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…This high amount of dense vegetation provides better conditions for nesting and shelter from predators, notably birds of prey (Rouibi et al, 2013;Gherib andLazli, 2016, 2017;Elafri et al, 2016). This variation in the pattern of waterbird abundance and richness between wintering and breeding seasons in Lake Tonga was also described by Elafri et al (2016) and Loucif et al (2020), but numbers were considerably lower than those reported in this study.…”
Section: Discussionsupporting
confidence: 88%
“…One particular pattern was that Shannon and equitability indexes were highest during autumn, displaying a perfect balance throughout this period and corresponding to the arrival of several wintering and migrating birds (such as tufted duck, greylag goose, marbled teal, common shelduck, pied avocet, and Northern lapwing). Values obtained during this autumnal season were close to those of studies in other coastal wetlands such as Garaet Hadj Tahar (Metallaoui and Houhamdi, 2010), Lake Beni-Belaid and El Kennar Marsh (Mayache, 2008) but higher compared to those of Elafri et al (2016) and Loucif et al (2020) in the same site. Through wintering period Shannon diversity index and Equitability were lower comparared with Simpson index which was due to the high abundance of coot in the two first wintering seasons as reported by Elafri et al (2016) and the Eurasian wigeon in the third one.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations